Occupational wellbeing on playgrounds: Parents’ views on children with coordination disorder - Anika Stoffel; Johanna Linimayr; Christina Schulze (Scandinavian Journal of Occupational Therapy, 2025)
Background: Outdoor play on playgrounds is fundamental for children’s health and wellbeing. However, the usability of playgrounds can influence children’s play, resulting in potential barriers for children with developmental coordination disorder (DCD). Aim: This study describes the wellbeing of children with DCD and the usability of playgrounds, from their parents’ views. Methods: A cross-sectional design was applied. 35 parents of children (4–7 years) with DCD answered a questionnaire, which was analysed descriptively. Results: The results show that parents perceived public playgrounds as valuable play spaces contributing to their children’s occupational wellbeing. Parents reported that their children played in a broad variety of ways, but playground usability was limited concerning the domains of competence, identity, and belonging. Children’s play competence was perceived as being hindered, including in the child’s individual play preferences (e.g. climbing, swinging, or balancing). Conclusion: An increased understanding on how the usability of playgrounds relates to occupational wellbeing for children with DCD could contribute to an enhancement of occupation-based clinical practice.